Investigate the causes of Islamic influence in Central Asia and its possible consequences - محسن اسلامی; بهروز ایاز (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2017)
Two years after the creation ISIS, the group moved towards Central Asia. This advancement raised many questions and worried analysts. This paper tries to answer the question that: What are the causes for the advancement of ISIS in Central Asia? The hypothesis of this paper is that some regional factors such as poverty, underdevelopment, political and economic instability, spread of extremism among some Muslims, rich mineral resources of this area, the two fundamentalist Muslim communities (Pakistan and Afghanistan) as the neighboring countries, Russian influence, the presence of Muslims in the West China (Xinjiang province) and most importantly ISIS strategy for Internationalization led to the advancement of this group in the region.